Can discrepancies between impulsive and reflective processes be associated with movement behavior among the elderly? The facilitating role of inhibitory control. (November 2022) - Oliveira, Gledson Tavares Amorim; Elsangedy, Hassan Mohamed; Vivas, Andrés; Fontes, Eduardo Bodnariuc
Abstract: Physical activity participation remains a global public health challenge, with 8 out of 10 older adults failing to meet the minimum physical activity recommendations, and it is also associated with an increased risk of cardiovascular disease, cognitive impairment, and mortality. Strategies to promote physical activity are primarily focused on socio-cognitive factors, and their effectiveness is limited. According to dual-process theories, physical activity is related with impulsive/implicit (i.e., emotions) and reflective/explicit (i.e., perceived advantage) processes; however, implicit-explicit discrepancy (IED) may impair movement behavior. In addition, cognitive inhibitory control may have r direct relationship with IED situations since it determines which of these processes predominates in the regulation of individual's behavior. Nonetheless, these outcomes in physical activity behavior among older adults have received little attention. In this study, we associate IED with physical activity and sedentary behavior as measured by accelerometers, and investigate the moderator role of inhibitory control in this association. In this cross-sectional study, 94 older adults were assessed for implicit and explicit attitudes, inhibitory control, and movement behavior using accelerometers over the course of seven days. A higher magnitude of the IED was linked to less moderate-to-vigorous physical activity (MVPA) and daily steps. Interestingly, a higher light physical activity was associated with a direction of the IED with more positive explicit attitudes. Furthermore, in older adults with higher inhibitory control, a direction of the IED with more positive explicit attitudes than implicit attitudes was associated with higher MVPA. Our findings suggest that IED may be important factor in the physical activity behavior of older adults. Furthermore, a higher inhibitory control appears to override an impulsive negative response, enabling a more positive reflective assessment of physical activity to serve as the main driver of an active lifestyle. Highlights: Implicit-explicit discrepancy impairs the physical activity of the elderly. Explicit attitudes that are more positive than implicit are associated with a higher light physical activity. A high inhibitory control may favor the prevalence of positive explicit attitudes that guide a more active lifestyle.